Konsumsi Zat Gizi Mikro dan Pengetahuan Penderita Hipertensi di Kota Bengkulu - Meirine Putri Zurli; Jumiyati Jumiyati; Ahmad Rizal (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Hypertension, or often referred to as high blood pressure is an increase in blood pressure that occurs continuously and is not normal in many arteries. High blood pressure can be caused by several factors, namely, foods that are high in salt, fatty foods, the habit of consuming coffee, lack of exercise or physical activity, and stress. The purpose of this study was to look at Consumption of Micronutrients and Knowledge of Hypertension Sufferers in Bengkulu City. Method: This type of research is descriptive and uses a cross-sectional design, and uses total sampling. The number of samples was 48 respondents with hypertension. Results: out of 48 samples there were 48 hypertensive patients, there was an average value for consumption of Vitamin D, namely 18.3 mcg, Sodium, which was 2,700.3 mg, Calcium, which was 1,013.6 mg, who was 40 years old. -44 years, namely (37.5%), those with high school education, namely (68.7%), those with housewife work, namely (89.6%), and those who have good knowledge, namely (43.75%), and those who have bad knowledge (56.25%). Conclusion: Consumption of Calcium is still low, Consumption of Vitamin D is sufficient, and Consumption of Sodium is almost entirely excessive and Knowledge is mostly still poor (low).